Study on Vegetation Water Requirements of Robinia pseudoacacia and its mixed plantation in Loess Gully Region. Issue 1 (January 2021) - Fu, Chong; Song, Xiaoyu; Li, Lanjun; Li, Huaiyou
Abstract: By calculating the vegetation water requirements( ETC ) of the typical plantations of Robinia pseudoacacia and Robinia pseudoacacia-Platycladus orientalis mixed plantation in the Loess Gully Region and analysing the coupling relationship between rainfall(P) and water requirements of each plantation, thereby scientifically guides local tree planting and afforestation, and better vegetation restoration.The Penman-Monteith formula is used to calculate the reference crop evapotranspiration in the study region, and then the double crop coefficient method is used to calculate the daily ETC of Robinia pseudoacacia and its mixed plantation in different hydrological years. The result shows that from dry year to normal year, the ETC-RP-CO is less than ETC-RP by 48.8 mm and 52.2 mm respectively, and the growth season accounts for the largest proportion. The ETC-RP-PO and ETC-RP are not satisfied in most months of the growth season. Among them, the initial period and the development period of the growth season are the largest, with the largest water requirements deficits( D ) reaching 58.65mm, 51.32mm (dry year) and 106.21mm, 93.18mm (normal years).The ETC of two plantation increases from dry year to normal year.And the D also increases when vegetation water requirements satisfaction( S ) increases, but the increase rate is expressed ETC > S > D .